A retrospective cohort study of mortality rates in patients with an opioid use disorder treated with implant naltrexone, oral methadone or sublingual buprenorphine. (4th May 2019) - Kelty, Erin; Joyce, David; Hulse, Gary
ABSTRACT: Background : Sustained release naltrexone has been shown to be a safer alternative to oral naltrexone in terms of mortality in patients with an opioid use disorder; however, a direct large-scale comparison has not been made between sustained release naltrexone and the more popular opioid pharmacotherapies: methadone and buprenorphine. Objective : To examine and compare mortality rates in patients with an opioid use disorder treated with implant naltrexone, methadone, and buprenorphine. Methods : Patients treated with implant naltrexone ( n = 1461, 35.6% female), methadone ( n = 3515, 33.3% female), or buprenorphine ( n = 3250, 34.5% female) for the first time between 2001 and 2010 in Western Australia (WA) were cross-matched against the WA Death Registry. Results : Crude mortality rates in patients treated with methadone (8.1 per 1000 patient years (ptpy) (HR:1.13, CI:0.82–1.55, p = 0.447) or buprenorphine (7.2 ptpy) (HR:1.01, CI:0.72–1.42, p = 0.948) were not significantly different to those treated with implant naltrexone (7.1 ptpy). Similarly, no differences were observed between the three treatments in terms of cause-specific or age-specific mortality. However, high rates of mortality were observed in methadone-treated patients during the first 28 days of treatment (HR:8.19, CI:1.08–62.21, p = 0.042) compared to naltrexone-treated patients. Female patients treated with methadone (HR:2.96, CI:1.34–6.51, p = 0.007) also experienced a higher overall mortality rate compared to naltrexone-treated patients. Conclusions : Crude mortality rates are comparable in patients with an opioid use disorder treated with implant naltrexone, methadone, and buprenorphine. However, implant naltrexone may be associated benefits during the first 28 days of treatment and in female patients compared to methadone.